(untitled) (Bangladesh Journal of Agricultural Research, 2007)
Based on the seed set ratio, levels of self-incompatibility in the genotypes varied from 8.9 to 90.1 percent. The genotypes Tori-7, M-27, Din-2, Din-7, Com-5, OTBC-0293, and Bhawani showed high levels of self-incompatibility. Ten genotypes including variety TS-72 showed intermediate level of self-incompatibility. Based on the number of pollen tubes in the style, the cultivars Dhali and Sampad were grouped as self-compatible, while the genotypes PT-303, PT-30, OTBC-20, OTBC-58, OTBC-0394, NK-1, FRD-1, and Com-5 were intermediate. The other genotypes were classed as self-incompatible. Considering seed set analysis and pollen tube growth behaviour study, six genotypes, namely Tori-7, M-27, Din-2, Din-7, Bhawani, and OTBC-0293 demonstrated high level of self-incompatibility. There was also success on bud pollination for producing SI seeds in those lines. Bangladesh J. Agril. Res. 32(2) 2007:235-246.